2006
DOI: 10.1185/030079906x100212
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance plus reliever budesonide/formoterol compared with a higher maintenance dose of budesonide/formoterol plus formoterol as reliever in asthma:an efficacy and cost-effectiveness study

Abstract: Compared with the 2 x 2 FIX + F treatment the use of budesonide/formoterol was 30-40% lower in the SMART groups while maintaining equal ACQ(5) scores. Daily asthma control improved equally with 2 x SMART compared to 2 x 2 FIX + F with a reduction in asthma medication cost. The one dose once daily maintenance treatment (1 x SMART) resulted in a low level of treatment failure (exacerbations) but led to more days with symptoms. Therefore, a daily dose of two inhalations seems to be the lowest appropriate dose in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 25 publications
5
39
1
2
Order By: Relevance
“…However, changes in maintenance treatment in the Budesonide/formoterol SMART arm or addition of other controller therapy were not allowed. The lack of significant differences between Budesonide/formoterol SMART and CBP with respect to time to severe exacerbation and exacerbation rates in this study and in other real-life studies (16,17) is therefore likely to reflect a lack of statistical power. This is linked to the low incidence of events in the CBP arm because of the inclusion of well-controlled patients and the added flexibility of treatment with a free choice of multiple maintenance therapies or the addition of formoterol as reliever therapy to the CBP arm, which is also effective in reducing exacerbation risk (18).…”
Section: Discussioncontrasting
confidence: 58%
“…However, changes in maintenance treatment in the Budesonide/formoterol SMART arm or addition of other controller therapy were not allowed. The lack of significant differences between Budesonide/formoterol SMART and CBP with respect to time to severe exacerbation and exacerbation rates in this study and in other real-life studies (16,17) is therefore likely to reflect a lack of statistical power. This is linked to the low incidence of events in the CBP arm because of the inclusion of well-controlled patients and the added flexibility of treatment with a free choice of multiple maintenance therapies or the addition of formoterol as reliever therapy to the CBP arm, which is also effective in reducing exacerbation risk (18).…”
Section: Discussioncontrasting
confidence: 58%
“…The difference between the single combination inhaler and SABA as relievers is the simultaneous administration of a corticosteroid in the combination, suggesting that the relief corticosteroid may play a key role in reducing exacerbations. A recent open study showed that single inhaler therapy with the combination inhaler as rescue therapy was similar to using the same fixed-dose combination therapy with formoterol alone as rescue therapy in terms of the number of additional puffs needed to control symptoms [28]. In a recent large double-blind study which compared formoterol to budesonide/formoterol as reliever therapy [29], the combination inhaler was significantly better than using formoterol alone as reliever in reducing exacerbations, providing strong support for the idea that the ''as required'' additional use of corticosteroid plays a critical role in reducing asthma exacerbations and improving asthma control.…”
Section: Safety Of Labamentioning
confidence: 99%
“…To date, this approach has reduced exacerbations when compared with a higher dose of inhaled corticosteroid, [14][15][16] or an equivalent or higher dose of a combined long-acting β 2 -agonist and corticosteroid used for maintenance treatment only. [16][17][18][19] As in most studies, patients known to have poor adherence to inhaled corticosteroid treatment were excluded from participating in these studies, and reported adherence rates during the studies were high, ranging from 85-99%.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%